Frequency of Perinatal Outcomes in Patients with Major Degree Placenta Previa - Jadoon, Sumbal; Fawad, Anisa; Qazi, Laiba; Masooma Syed (Indus Journal of Bioscience Research, 2025)
Background: Major degree placenta previa, characterized by complete coverage of the cervical os by the placenta, poses significant risks to both mother and fetus. Despite improvements in obstetric practice, it remains a leading cause of prematurity, perinatal morbidity, and mortality. Objective: To determine the frequency of perinatal outcomes in patients with major degree placenta previa. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was carried out from January 2025 to May 2025 at the Department of Obstetrics and Gynaecology, Ayub Teaching Hospital, Abbottabad. Methodology: A total of 113 women aged 20–40 years with ultrasound-confirmed major degree placenta previa were enrolled. Patients with pregnancy-induced hypertension, eclampsia, gestational diabetes, or fetal anomalies were excluded. Baseline demographic details were recorded, and perinatal outcomes were documented. Results: Prematurity was the most frequent outcome, affecting 72 patients (63.7%), while 41 (36.3%) delivered at term. NICU admission was required in 28 cases (24.8%). Birth asphyxia and neonatal death were observed in 20 patients each (17.7%). Intrauterine fetal death occurred in 14 cases (12.4%). Higher rates of prematurity and NICU admissions were seen in mothers >30 years, while low maternal BMI was significantly associated with intrauterine fetal death (p=0.046). Conclusion: Our study has concluded that major degree placenta previa is strongly associated with adverse perinatal outcomes, especially prematurity, neonatal mortality, and NICU admission.